Cryptocurrency in Islamic View: Sentiment Analysis Method Approach - Birjaman, Muhammad Iqbal; Marits, Shofi Arofatul; Herman, Sebastian (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Islamic economics focuses on realizing Islamic ideals, rahmatan lil 'alamin, which aims to provide goodness, prosperity and well-being. Halal (Positive) and haram (negative) aspects in the realm of cryptocurrency. Based on an extensive review of 23 relevant journals, this research aims to analyze the literature and explore the implications of cryptocurrency in relation to Islamic principles. This research focuses on key variables such as compliance with Sharia, riba (usury), gharar (uncertainty), and transparency. By reviewing existing literature and considering the perspective of Islamic scholars and law, this paper aims to determine whether cryptocurrency is permitted or prohibited from an Islamic perspective. These findings will contribute to the ongoing discourse around the compatibility of cryptocurrencies with Islamic finance and ethics. This study emphasizes the importance of addressing halal and haram issues and implications in the cryptocurrency ecosystem. Ultimately, this research aims to provide insights and recommendations for scholars and practitioners in the field of Islamic finance and cryptocurrency.